Wiener criterion for relaxed Dirichlet problem relative to Riemannian p-homogeneous Dirichlet forms - Biroli, M.; Dal Fabbro, F.; Marchi, S. (Український математичний вісник, 2008)
We give a Wiener criterion for the relaxed Dirichlet problem relative to a Riemannian p-homogeneous Dirichlet form.